2020
DOI: 10.1101/2020.06.08.141127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability of SARS-CoV-2 Phylogenies

Abstract: The SARS-CoV-2 pandemic has led to unprecedented, nearly real-time genetic tracing due to the rapid community sequencing response. Researchers immediately leveraged these data to infer the evolutionary relationships among viral samples and to study key biological questions, including whether host viral genome editing and recombination are features of SARS-CoV-2 evolution. This global sequencing effort is inherently decentralized and must rely on data collected by many labs using a wide variety of molecular and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 76 publications
2
65
0
Order By: Relevance
“…Whereas UShER appears to be robust to a single systematic error present in fewer than five samples ( Figure 2), a single systematic error present in all 10 samples had a similar overall effect on placement accuracy as 50% missing data in error-free sequences. Consistent with our previous work 37,38 , addition of two perfectly correlated systematic errors can drastically affect UShER performance ( Figure S1). Systematic errors should be rigorously identified and removed before sample placements are performed.…”
Section: Usher Accurately Places Simulated Sars-cov-2 Samplessupporting
confidence: 91%
See 3 more Smart Citations
“…Whereas UShER appears to be robust to a single systematic error present in fewer than five samples ( Figure 2), a single systematic error present in all 10 samples had a similar overall effect on placement accuracy as 50% missing data in error-free sequences. Consistent with our previous work 37,38 , addition of two perfectly correlated systematic errors can drastically affect UShER performance ( Figure S1). Systematic errors should be rigorously identified and removed before sample placements are performed.…”
Section: Usher Accurately Places Simulated Sars-cov-2 Samplessupporting
confidence: 91%
“…Second, systematic error, where the same apparent variant is introduced into many sequences, are present in some SARS-CoV-2 sequences and have the potential to affect phylogenetic inference because they appear as inherited mutations 37,38 . Whereas UShER appears to be robust to a single systematic error present in fewer than five samples ( Figure 2), a single systematic error present in all 10 samples had a similar overall effect on placement accuracy as 50% missing data in error-free sequences.…”
Section: Usher Accurately Places Simulated Sars-cov-2 Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our singleton removal strategy is further justified by a recent study that has shown that lab-specific sequencing practices yield mutations that have been observed predominantly or exclusively by single labs. These can in turn affect the phylogeny reconstruction process (26). The authors provide regularly updated masking recommendations at https://github.com/W-L/ProblematicSites_ SARS-CoV2/blob/master/problematic_sites_ sarsCov2.vcf.…”
Section: Data Preparation and Analysis Pipelinementioning
confidence: 99%